Open housing drives the expression of immune response genes in the nasal mucosa, but not the olfactory bulb - Piotrowski, Carolin (PLoS One, 2017)
Nasal mucosa and olfactory bulb are separated by the cribriform plate which is perforated by olfactory nerves. We have previously demonstrated that the cribriform plate is permissive for T cells and monocytes and that viruses can enter the bulb upon intranasal injection by axonal transportation. Therefore, we hypothesized that nasal mucosa and olfactory bulb are equipped to deal with constant infectious threats. To detect genes involved in this process, we compared gene expression in nasal mucosa and bulb of mice kept under specific pathogen free (SPF) conditions to gene expression of mice kept on non-SPF conditions using RNA deep sequencing. We found massive alterations in the expression of immune-related genes of the nasal mucosa, while the bulb did not respond immunologically. The absence of induction of immune-related genes in the olfactory bulb suggests effective defence mechanisms hindering entrance of environmental pathogens beyond the outer arachnoid layer. The genes detected in this study may include candidates conferring susceptibility to meningitis.